2004
DOI: 10.1370/afm.62
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients With Hepatitis C in a Community Population: Diagnosis, Discussions, and Decisions to Treat

Abstract: BACKGROUND Chronic hepatitis C, a treatable condition caused by the hepatitis C virus (HCV), can be found in almost all primary care and community practices. The rate of hepatitis C treatment is low, however. This study explores the frequency of hepatitis C treatment, documented discussions of treatment consideration, and the reasons treatment may not be offered in a community population. METHODSThis study is a retrospective medical record review of care provided to all patients in Olmsted County, Minn, who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
(38 reference statements)
4
45
0
3
Order By: Relevance
“…Rowan et al [13] in a series of 580 Veterans, and Muir and Provenzale [12] in a series of 100 Veterans, showed that 70% and 68%, respectively, of their HCV patients had not been considered as eligible for therapy. Rocca et al [17] retrospectively reviewed a series of 366 HCV patients listed in the Olmsted County Hepatitis C registry. For these patients, a discussion on treatment was performed for only 234 patients (64%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rowan et al [13] in a series of 580 Veterans, and Muir and Provenzale [12] in a series of 100 Veterans, showed that 70% and 68%, respectively, of their HCV patients had not been considered as eligible for therapy. Rocca et al [17] retrospectively reviewed a series of 366 HCV patients listed in the Olmsted County Hepatitis C registry. For these patients, a discussion on treatment was performed for only 234 patients (64%).…”
Section: Discussionmentioning
confidence: 99%
“…In this population, the most common contraindication was psychosocial factors [12]. Although the findings in HCV-infected US Veterans may not be directly applicable to other HCV populations (because they are more likely than HCV-infected US non-Veterans to have a history of alcoholism, active substance abuse, posttraumatic stress disorder and antidepressant therapy [14]), a few studies in the general population in the United States also reported that many patients were not eligible for therapy [15][16][17]. To date, such figures are not available for Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The study of management of hepatitis C patients 19 brought calls for advocacy and safety nets to facilitate care 20,21 and useful additional clinical information for increasing our awareness and effi cacy in case fi nding in primary care. 22,23 The study of medical errors by Elder et al 23 spawned a research agenda 24 and an articulation of the challenges of measuring errors of omission.…”
Section: Track Discussion Of Research Reportsmentioning
confidence: 99%
“…Prior studies have shown that HCV patients without access to a specialist are less likely to be treated (Rocca et al, 2004). This is significant from a clinical and public health standpoint because almost half of patients treated with the current standard of care (6-18 months of therapy with pegylated interferons and ribavirin) achieve long term cure with a resultant improvement of liver-related mortality rate that approximates the one experienced in the general population (Simin et al, 2007;Veldt et al, 2007;Kasahara et al, 2004).…”
Section: Closing the Gap Of Access To Specialty Carementioning
confidence: 99%